Development of Mangrove Revegetation in Increasing the Availability of Food Materials from the Existence of Association Biota in Central Lombok - M. Akhyar Rosyidi; Agil Al Idrus (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Mangrove forest is an ecosystem that functions as a habitat for various animals and biota, but mangrove damage has a negative impact on the diversity of associated biota and the availability of food materials. This study aims to determine the development of mangrove revegetation in increasing the availability of food materials from the presence of associated biota in Central Lombok. Primary data collected from quadratic sampling along the line transects were further analyzed to determine mangrove diversity and dispersion indices as well as macrofauna diversity, uniformity, dominance and abundance indices. The results of the analysis of mangroves, the highest diversity index was in Dondon Beach at 1.52, Tanjung Batutiang at 1.49 and Gili Perigi at 1.42, while the highest dispersion index at Gili Perigi at 0.61, Tanjung Batutiang at 0.55 and Dondon Beach at 0.51. Furthermore, the results of macrofauna analysis showed that the highest diversity index was in Tanjung Batutiang at 2.59, Dondon Beach at 2.51 and Gili Perigi at 2.49, the highest uniformity index at Tanjung Batutiang at 0.82, Dondon Beach at 0.80 and Gili Perigi at 0.79, the highest dominance index at Tanjung Batutiang at 0.91, on Gili Perigi and Dondon Beach of 0.89, the highest abundance index on Dondon Beach of 3.05, on Gili Perigi and Dondon Beach of 2.71. The conclusion of this study is that mangrove revegetation has succeeded in increasing the availability of food material in terms of the presence of macrofauna in Central Lombok.